2012
DOI: 10.7763/ijbbb.2012.v2.79
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Bioconservation and Biodiversity in Turkey

Abstract: Abstract-Biodiversity represents the basis of all life on our planet or in a specific area. It is clear that natural resources do not last forever. Turkey is one of the most biologically diverse countries in the temperate zone. More than one third of species found in Turkey are endemic, native to the region. So Turkey is like a kind of small continent in terms of biodiversity. It is also rich as biodiversity with 120 mammals, 469 bird species, 130 reptiles, 400 fishes and 4000 endemic of 11000 plants species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Biodiversity presents the base of life in a specific area and over the world as well (Kahraman et al, 2012). In the Turkey, steppe rangeland is a matter of splendid biodiversity (Avci, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Biodiversity presents the base of life in a specific area and over the world as well (Kahraman et al, 2012). In the Turkey, steppe rangeland is a matter of splendid biodiversity (Avci, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Common bean has a great diversity of phenotypes in terms of seed size, colors and mineral composition, exposing the rich genetic diversity among the species (Papa et al 2005, Gonçalves Ceolin et al 2007. Breeders should pay attention to the importance of bioconservation and biodiversity (Kahraman et al 2012). A remarkable characteristic of common bean is a grand flexibility of seed coat and patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Kahraman et al (2012) reported that Turkey always has four seasons in a year. The country usually experiences four seasons simultaneously due to its climatic and geographical characteristics.…”
Section: Introductionmentioning
confidence: 99%